CD13 expression in B cell malignancies is a hallmark of plasmacytic differentiation. (10th September 2018) - Raimbault, Anna; Machherndl‐Spandl, Sigrid; Itzykson, Raphaël; Clauser, Sylvain; Chapuis, Nicolas; Mathis, Stéphanie; Lauf, Jeroen; Alary, Anne‐Sophie; Burroni, Barbara; Kosmider, Olivier; Fontenay, Michaela; Béné, Marie C.; et al.
Summary: The diagnosis of Waldenström Macroglobulinaemia (WM)/lymphoplasmacytic lymphoma (LPL) remains one of exclusion because other B‐cell lymphoproliferative disorders (B‐LPD), such as marginal zone lymphoma (MZL), can fulfil similar criteria, including MYD88 L265P mutation. It has been suggested that expression of the myeloid marker CD13 (also termed ANPEP) is more frequent in LPL than in other B‐LPD and has also been described on normal and malignant plasma cells. Here, CD13 expression was tested in a cohort of 1037 B‐LPD patients from 3 centres by flow cytometry. The percentage of CD13‐expressing cells was found to be variable among B‐LPD but significantly higher in WM/LPL (median 31% vs. 0% in non‐WM/LPL, P  < 0·001). In multivariate linear regression, CD13 expression remained significantly associated with a diagnosis of WM/LPL ( P  < 0·001). A cut‐off value of 2% of CD19 + cells co‐expressing CD13 yielded the best diagnostic performance for WM/LPL assertion. This was further improved by association with the presence or absence of IgM paraprotein. Finally, given that previously published transcriptomic data revealed no difference in CD13 (also termed ANPEP ) mRNA between normal and pathological B‐cells, the hypothesis of some post‐transcriptional regulation must be favoured. These results suggest that testing for CD13 expression in routine flow cytometry panels could help to discriminate WM/LPL from other B‐LPD.